2013
DOI: 10.4028/www.scientific.net/amr.815.415
|View full text |Cite
|
Sign up to set email alerts
|

Research and Application of Heat Transfer Fluids in Solar Thermal Power

Abstract: mproving the thermophysical properties of heat transfer fluid is always a research hotspot and difficult subject in the application of solar energy for medium and high temperature. The research and application of these heat transfer fluid, including steam, heat transfer oil, molten salt, air, liquid alloy and nanofluids, were summarized in this paper. After comparing their characteristics, it is found that molten salt, air and liquid alloy have greater application and development prospects. Future research dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Recent studies have confirmed suspending small particles in a fluid can improve its heat transfer performance [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In particular, the addition of small micrometer-scale particles (solid phase) to a working fluid (fluid phase) can improve its thermal conductivity and heat transfer coefficient [ 46 , 47 ]. Unfortunately, two-phase fluids containing micrometer-scale particles have a number of operational problems.…”
Section: Direct Solar Absorption Collectors and The Use Of Nanoflumentioning
confidence: 99%
“…Recent studies have confirmed suspending small particles in a fluid can improve its heat transfer performance [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In particular, the addition of small micrometer-scale particles (solid phase) to a working fluid (fluid phase) can improve its thermal conductivity and heat transfer coefficient [ 46 , 47 ]. Unfortunately, two-phase fluids containing micrometer-scale particles have a number of operational problems.…”
Section: Direct Solar Absorption Collectors and The Use Of Nanoflumentioning
confidence: 99%
“…The inclusion of low concentrations of well dispersed particles in traditional working fluids can significantly enhance their thermo-physical properties [6,7]. However, the inclusion of large particles in working fluids has resulted in sedimentation, increased flow resistance, accumulation and blockage of small flow channels that result in higher system pressure drops [8,9]. Because of these shortcomings, particle addition has failed to gain widespread acceptance.…”
Section: Introductionmentioning
confidence: 99%